2007
DOI: 10.1007/s10490-007-9073-0
|View full text |Cite
|
Sign up to set email alerts
|

A strategic analysis of surging Chinese manufacturers: The case of Galanz

Abstract: Chinese manufacturers, Strategic analysis, Internationalization, Galanz,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 26 publications
9
38
1
1
Order By: Relevance
“…Similar results have been reported in recent years using smaller samples and case studies (Ge and Ding 2008, Cardoza and Fornes 2011. This may indicate that: (i) the government supports (or has supported) only a group of tier 1, national champions, or chosen companies and/or industries in their internationalisation process, (ii) the Government supports (or has supported) the internationalisation of companies only to politically or economically strategic markets (like the US and the EU to acquire capabilities, or Africa for natural resources, for example), (iii) the Government supported the first wave of companies going abroad but as the number of firms grows this support tends to be less tangible, and/or (iv) there is a new breed of competitive networks or alliances based on the combination of complementary capabilities (Williamson and Yin 2009, Fornes and Butt Philip 2012, Williamson et al 2013 where the support of the government has not been a key element in their internationalisation process.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results have been reported in recent years using smaller samples and case studies (Ge and Ding 2008, Cardoza and Fornes 2011. This may indicate that: (i) the government supports (or has supported) only a group of tier 1, national champions, or chosen companies and/or industries in their internationalisation process, (ii) the Government supports (or has supported) the internationalisation of companies only to politically or economically strategic markets (like the US and the EU to acquire capabilities, or Africa for natural resources, for example), (iii) the Government supported the first wave of companies going abroad but as the number of firms grows this support tends to be less tangible, and/or (iv) there is a new breed of competitive networks or alliances based on the combination of complementary capabilities (Williamson and Yin 2009, Fornes and Butt Philip 2012, Williamson et al 2013 where the support of the government has not been a key element in their internationalisation process.…”
Section: Discussionsupporting
confidence: 92%
“…In the particular case of Chinese companies (as shown in the previous section), this interaction is evident in the support from the national and local governments to internationalise their operations (Cai, 1999;Rui & Yip, 2008) to which Matthews added that SMEs, in particular, have to find ways to offset risks like "joint ventures and other forms of collaborative partnership as a means of gaining entry to foreign markets" (2006: 18-19). Ge and Ding (2008) reached similar conclusions. This idea introduces the second objective of this paper, to analyse the effects (if any) of different ownership types and also of the financial support received from the state (two of the main characteristics of Chinese international firms and also part of the interaction between institutions and organisations).…”
supporting
confidence: 63%
“…Amongst 'newer' perspectives we also have Luo and Tung's (2007) (Ge and Ding, 2008;Popli and Sinha, 2014). However, the springboard perspective does not elucidate the post-springboard or post entry difficulties EMMs may encounter.…”
Section: Luo and Tung's (2007) Springboard Perspective And Mathews' (mentioning
confidence: 99%
“…Over time, EMMs may learn how to compete with DMMs in areas such as innovation and new product development. Based on interviews with Chinese managers, Ge and Ding (2008) found that the LLL framework provides a better explanation for the catch-up strategies of manufacturing EMMs, which start their international expansion by leverag ing linkages with DMMs to lower their production costs and achieve cost leadership, and over time may switch focus towards innovation or marketing capabilities as sources of competitive advantage. It is yet to be concluded whether differences between LLL and theories such as OLI are important or simply a matter of emphasis.…”
Section: Luo and Tung's (2007) Springboard Perspective And Mathews' (mentioning
confidence: 99%